Carbon dioxide fluxes and the dominant role of vegetation in recently created and reference Gulf Coast marshes - A. Muench; T. Elsey‐Quirk; J. R. White; R. D. DeLaune (Ecosphere)
Abstract Coastal wetlands are one of the most productive ecosystems on Earth with the capacity to sequester large amounts of carbon dioxide (CO2). Wetland loss due to anthropogenic and natural causes reduces the carbon (C) storage capacity and potentially releases previously fixed C in biomass and soil to the water column and atmosphere through decomposition. Coastal wetland restoration has the potential to mitigate some of the C losses depending on the balance of C fluxes. However, the role of vegetation and environmental conditions in governing rates of C accumulation in restoration sites is not well resolved. The purpose of this study was to examine seasonal C fluxes, specifically, gross ecosystem productivity (GEP), ecosystem respiration (ER), and net ecosystem exchange (NEE) of CO2 in unvegetated and vegetated (Spartina alterniflora) areas of a 2‐year old created marsh, and S. alterniflora and Spartina patens communities in a “natural” reference brackish marsh. S. alterniflora‐dominated areas were sinks for CO2 in both the newly created and reference marsh with an average CO2 uptake rate of 7.0 ± 1.0 μmol m−2 s−1. The unvegetated areas in the newly created marsh and S. patens areas in the reference marsh had approximately net neutral CO2 fluxes. S. alterniflora areas of the created marsh had similar carbon fluxes to that in the reference marsh, despite a much lower soil organic matter content. Because vegetation develops much faster than soil properties, restored marshes can be a C sink equivalent to natural marshes as soon as the marsh is vegetated. Ecosystem productivity and C assimilation in S. alterniflora areas of the reference marsh were enhanced by lower elevations (up to 6 cm) and higher soil bulk density (up to 0.28 g cm−3). At similar elevations, S. alterniflora in both the created and reference marshes was a greater C sink than S. patens areas of the reference marsh. Our findings illustrate that establishment of vegetation is critical to promoting C sink functions in created marshes and, notably, species do matter.